Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1074/jbc.m117.775643
|View full text |Cite
|
Sign up to set email alerts
|

Serotype-specific interactions among functional domains of dengue virus 2 nonstructural proteins (NS) 5 and NS3 are crucial for viral RNA replication

Abstract: Four serotypes of mosquito-borne dengue virus (DENV), evolved from a common ancestor, are human pathogens of global significance for which there is no vaccine or antiviral drug available. The N-terminal domain of DENV NS5 has guanylyltransferase and methyltransferase (MTase), and the C-terminal region has the polymerase (POL), all of which are important for 5'-capping and RNA replication. The crystal structure of NS5 shows it as a dimer, but the functional evidence for NS5 dimer is lacking. Our studies showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Thus, we focused our attention on the significance of these NS5 mutations in altering the epidemiologic fitness of DENV2. Indeed, previous studies have shown that mutations in NS5 compromise virus replication (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we focused our attention on the significance of these NS5 mutations in altering the epidemiologic fitness of DENV2. Indeed, previous studies have shown that mutations in NS5 compromise virus replication (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…RNAseq alignment analysis of DENV2 sequences. Raw Fastq files described above were used for analysis of frequencies and locations of nucleotide changes in DENV2 RNA using Geneious (version 9.1) software (Biomatters) as previously described (91).…”
mentioning
confidence: 99%
“…Extracted viral RNAs from supernatants of infected cells were used for viral cDNA synthesis and PCR amplification with DENV2 sequence-specific primers (91). PCR products were purified with an agarose gel (Zymo Research), and DNA sequencing was performed by GENEWIZ Inc. (South Plainfield, NJ).…”
mentioning
confidence: 99%
“…Most of the identified conserved epitopes (45 out of 55) were derived from NS5 and NS3 (25 and 20, respectively) (Fig 3), highlighting the potential biological importance of targeting these non-structural proteins. Both NS5 and NS3 are large DENV proteins, comprising about 900 and 618 residues respectively (lengths slightly vary across serotypes), which are multifunctional enzymes playing a critical role in viral replication [50][51][52]. The high conservation of the identified NS5 and NS3 epitopes across serotypes (Fig 3) indicates that the protein regions associated with them may be structurally/functionally important for DENV.…”
Section: Top Conserved Denv T Cell Epitopes In Ns3 and Ns5 Are Locatementioning
confidence: 99%